2005
DOI: 10.1111/j.1365-2826.2005.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Calcium Involvement in Pituitary Adenylate Cyclase‐Activating Polypeptide Stimulation of Growth Hormone and Gonadotrophin Secretion in Goldfish Pituitary Cells

Abstract: The involvement of intracellular Ca(2+) stores and their regulatory mechanisms in mediating pituitary adenylate cyclase-activating polypeptide (PACAP) stimulation of growth hormone (GH) and maturational gonadotrophin (GTH-II) secretion from goldfish pituitary cells was investigated using a cell column perifusion system. Pretreatment with caffeine abolished the GH and GTH-II responses to PACAP. Dantrolene attenuated PACAP-elicited GTH-II release but did not affect the GH response, whereas ryanodine and 8-bromo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 57 publications
(107 reference statements)
2
14
0
Order By: Relevance
“…Although both XeC and XeD were found to effectively inhibit IP 3 R-dependent Ca 2ϩ signaling, only XeD (1 M) was able to enhance GH and maturational gonadotrophin responses, processes that require RyR-dependent elevation of intracellular Ca 2ϩ concentration. In this study, only XeD (not XeC) enhanced activation of RyR-mediated CICR and, in turn, enhanced responses to GH response to pituitary adenylate cyclase-activating polypeptide, a finding which the authors called "surprising" (Sawisky and Chang, 2005). We propose that our new finding of the unique bifunctional activity of XeD toward blocking IP 3 R and activating RyR1 can largely account for the results of Sawisky and Chang.…”
Section: Fig 6 Xed Mobilizes Casupporting
confidence: 60%
See 1 more Smart Citation
“…Although both XeC and XeD were found to effectively inhibit IP 3 R-dependent Ca 2ϩ signaling, only XeD (1 M) was able to enhance GH and maturational gonadotrophin responses, processes that require RyR-dependent elevation of intracellular Ca 2ϩ concentration. In this study, only XeD (not XeC) enhanced activation of RyR-mediated CICR and, in turn, enhanced responses to GH response to pituitary adenylate cyclase-activating polypeptide, a finding which the authors called "surprising" (Sawisky and Chang, 2005). We propose that our new finding of the unique bifunctional activity of XeD toward blocking IP 3 R and activating RyR1 can largely account for the results of Sawisky and Chang.…”
Section: Fig 6 Xed Mobilizes Casupporting
confidence: 60%
“…In a recent study, Sawisky and Chang (2005) examined the important role of intracellular Ca 2ϩ stores in regulating the actions of pituitary adenylate cyclase-activating polypeptide necessary for the release of growth hormone (GH) and maturational gonadotrophin secretion from goldfish pituitary cells. Although both XeC and XeD were found to effectively inhibit IP 3 R-dependent Ca 2ϩ signaling, only XeD (1 M) was able to enhance GH and maturational gonadotrophin responses, processes that require RyR-dependent elevation of intracellular Ca 2ϩ concentration.…”
Section: Fig 6 Xed Mobilizes Camentioning
confidence: 99%
“…We have shown that the CCK-AR antagonist dexloxiglumide significantly blocked the enhancement effect of CCK-8S on the contractile response of antral strips and the [Ca 2+ ] i level of SMCs, while the CCK-BR antagonist L-365,260 had little effect, indicating that CCK-AR instead of CCK-BR plays a major role in the gastric antrum. Elevation in the [Ca 2+ ] i concentration is an important function in the regulation of many cellular processes and can be achieved by release from internal stores, calcium entry across the plasma membrane, or both [24, 25]. The Ca 2+ -ATPase inhibitor TG and the [Ca 2+ ] i chelator BA were used in our experiment to examine the role of intracellular calcium stores and intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence that not only the structure, but the functions of PACAP have also been conserved. Among others, PACAP stimulates TSH release from the bullfrog pituitary (Okada et al 2007), regulates melanotrope cell activity in Xenopus (Kidane et al 2007), influences gonadotrophin secretion in goldfish pituitary cells (Sawisky and Chang 2005), affects food intake in chick and goldfish (Jozsa et al 2006;Matsuda et al 2006;Matsuda and Maruyama 2007), has muscle relaxant activity in fish (Matsuda et al 2000), enhances memory functions and is involved in rhythmical functions in chicken (Jozsa et al 2005;Nagy and Csernus 2007) and regulates neuronal development in zebrafish (Wu et al 2006).…”
Section: Introductionmentioning
confidence: 99%